Spherical Cubic Fuzzy Extended TOPSIS Method and Its Application in Multicriteria Decision-Making. (25th June 2021) - Tehreem,; Hussain, Amjad; Alsanad, Ahmed; A. A. Mosleh, Mogeeb
Abstract : This paper aims to propose a new methodology for spherical cubic fuzzy (SCF) multicriteria decision-making (MCDM) utilizing the TOPSIS method that uses incomplete weight information. At first, the maximum deviation model is suggested to determine the criteria of weight values. An MCDM methodology is introduced using SCF information, based on the proposed method. Also, to validate the effectiveness of the proposed information, a numerical example is given. Finally, a comprehensive and structured analysis of existing work in comparison with previous work is given.